Rising import demand in China: Cui bono and why? - Rolf J. Langhammer (Kiel Institute for the World Economy (IfW), 2011)
The paper measures income elasticities of demand for manufacturing imports in China since 1990 disaggregated by major trading partners such as the US, Japan, Germany and rest of the EU. German exporters seem to have benefited from the hightest demand elasticities. The paper proposes explanatory factors such as a high degree of integration in international production chains and higher presence of foreign direct investment in China compared to partner countries responsible for the German success.
Keywords: F14; 330; Manufactured Imports; China Income Demand; Elasticities; Industriegüteraußenhandel; Importnachfrage; Einkommenselastizität; China; Exportindustrie; USA; Japan; Deutschland; EU-Staaten